Vous êtes sur la page 1sur 2

1 J y cot α A tan α sin α x α I 0 cos
1 J
y cot α
A tan α
sin α
x
α I
0 cos α
1

 

α

π

π

π

π

π

3π

6

4

3

2

2

sin α

1

√ 2
2
√ 3
3

2

 

2

2

cos α

√ 3
3
√ 2
2

1 2

 

2

2

tan α

√ 3
3

3

3

cot α

3

√ 3
3

 

3

 

sin(π α) = sin α cos(π α) = cos α tan(π α) = tan α cot(π α) = cot α

sin(π + α) = sin α cos(π + α) = cos α tan(π + α) = tan α cot(π + α) = cot α

sin(α) = sin α cos(α) = cos α tan(α) = tan α cot(α) = cot α

sin π cos π tan π cot π

2

2

2

2

α = cos α

α = sin α

α = cot α

α = tan α

sin 2 a + cos 2 a = 1

1

1 cos 2 a

1 + cot 2 a =

+ tan 2 a =

1

sin 2 a

cos 2a = cos 2 a sin 2 a

= cos 2a = 1 2 sin 2 a sin 2a = 2 sin a cos a 2 tan a

cos 2a

2 cos 2 a 1

tan 2a =

1 tan 2 a

cos(a + b) = cos a cos b sin a sin b cos(a b) = cos a cos b + sin a sin b sin(a + b) = sin a cos b + cos a sin b sin(a b) = sin a cos b cos a sin b tan a + tan b

tan(a + b)

=

tan a tan b tan a tan b

1

1

+ tan a tan b

tan(a b) =

sin p + sin q = 2 sin p + q cos p q

2 2

sin p sin q = 2 cos p + q sin p q

cos p + cos q =

cos p cos q =

2 2

2

2

2 cos p + q cos p q

2 2

2 sin p + q sin p q

cos 2 a = 1 + cos 2a

2

sin 2 a = 1 cos 2a

2

1

sin a sin b = 2 (cos(a + b) + cos(a b))

sin a cos b = 1

cos a cos b =

2

1

(sin(a + b) + sin(a b))

2 (cos(a + b) + cos(a b))

sin x = sin a

cos x = cos a

x

x = π a + 2

= a + 2kπ

= a + 2kπ

x = a + 2

x

tan x = tan a x = a +

k Z

k Z

k Z

y

3

3

3

1

J

3

3

3

3

C (2π/3)

B (3π/4)

A (5π/6)

3

2 C(π/3)

B(π/4)

3

3

2

2

1

2

A(π/6)

3

2

1

O

1 2 I

2

2

2

3

x

 

2

2

2

A (7π/6)

0

1

A (11π/6)

3

1

2

2

2

2

3

B (5π/4)

B (5 π/ 4) B (7 π/ 4) 3

B (7π/4)

3

C (4π/3)

3

C (5π/3)